2003
DOI: 10.1083/jcb.200306009
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of mitotic kinesin-like protein 2 by polo-like kinase 1 is required for cytokinesis

Abstract: We have investigated the function of mitotic kinesin-like protein (MKlp) 2, a kinesin localized to the central spindle, and demonstrate that its depletion results in a failure of cleavage furrow ingression and cytokinesis, and disrupts localization of polo-like kinase 1 (Plk1). MKlp2 is a target for Plk1, and phosphorylated MKlp2 binds to the polo box domain of Plk1. Plk1 also binds directly to microtubules and targets to the central spindle via its polo box domain, and this interaction controls the activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
337
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 293 publications
(363 citation statements)
references
References 67 publications
(94 reference statements)
25
337
1
Order By: Relevance
“…Another important protein of this complex is PLK1 (polo-like kinase 1) which binds to microtubules and interacts with MKLP2. Phosphorylation of MKLP2 by PLK1 is required for the localization of PLK1 to the central spindle during anaphase and telophase and the complex of these two proteins is necessary for the completion of cytokinesis [26]. It is also shown that PLK1 is important for the binding of ECT2 to CYK-4 and its recruitment to the midzone, thus promoting the initiation and completion of cytokinesis.…”
Section: Early Cytokinesismentioning
confidence: 99%
See 1 more Smart Citation
“…Another important protein of this complex is PLK1 (polo-like kinase 1) which binds to microtubules and interacts with MKLP2. Phosphorylation of MKLP2 by PLK1 is required for the localization of PLK1 to the central spindle during anaphase and telophase and the complex of these two proteins is necessary for the completion of cytokinesis [26]. It is also shown that PLK1 is important for the binding of ECT2 to CYK-4 and its recruitment to the midzone, thus promoting the initiation and completion of cytokinesis.…”
Section: Early Cytokinesismentioning
confidence: 99%
“…Microtubule-associated proteins PRC1 [13,14] Centralspindlin complex CYK-4 [2,15] MKLP1 [2,15] Chromosome passenger complex INCENP [16,17] Survinin [16,17] Borealin [16,17] Aurora B [16,17] ESRCTs and associated proteins CEP55 [30][31][32] TSG101 [31,32] ALIX [31,32] CHMP1B [33] Spastin [33] CHMP4B [31,32,34] FYVE-CENT [34] TTC19 [34] Kinesins KIF4A [14] MKLP2 [17] MPP1 [22] KIF14 [23] KIF13A [34] Additional proteins NuSAP [18] Orbit [19] ASP [20] TBCD [21] ECT2 [24] FIP3 [25] PLK1 [26,27] Septins [28] Anillin [29] during anaphase and cytokinesis and is important for the last step of abscission. CEP55 binds directly MKLP1 and is controlled by centralspindlin, since knockdown of centralspindlin abolishes CEP55 from the midbody [30].…”
Section: The Abscission Step Of Cytokinesismentioning
confidence: 99%
“…This could be attributed to the presence of additional motor proteins with similar function to CHO1 at the spindle midzone. It has recently been reported that Rab6-KIFL (MKLP2: Hill et al, 2000;Neef et al, 2003) and PMM1 (Abaza et al, 2003) at the central spindle contain the microtubule bundling activity and are required for cytokinesis. Simultaneous elimination of all three motors may result in complete disorganization of central spindles and inhibition of cleavage furrow formation.…”
Section: Role Of Cho1 In Cytokinesismentioning
confidence: 99%
“…Isolated midbodies contain at least 158 different molecules (Skop et al, 2002); some of those might be responsible for maintaining the structural integrity of the midbody by connecting molecules in the midbody. Possible candidates might be PRC1, Rab6-KIFL, or MPP1, which were shown to bundle midzone microtubules (Jiang et al, 1998;Mollinari et al, 2002;Abaza et al, 2003;Neef et al, 2003). One possible scenario is that the T3 sequence of CHO1 is directly involved in association of CHO1 with those midbody components.…”
Section: Role Of the Nls-containing Regionmentioning
confidence: 99%
“…The role of rabkinesin6 as a rab6A-specific effector during interphase was recently challenged by the finding that rabkinesin6 does not colocalize with rab6 and is only present in minute amounts in interphase cells. In contrast, rabkinesin6 is greatly up-regulated during mitosis where it plays a role in cytokinesis (Hill et al, 2000;Fontijn et al, 2001;Neef et al, 2003). Nevertheless, the specific binding of rabkinesin6 to rab6A but not A' is consistent with the ability of rab6A but not A' to induce Golgi-to-ER recycling when overexpressed as a GTP-restricted mutant (Echard et al, 2000).…”
mentioning
confidence: 97%